БЎЛАЖАК МУСИҚА ТАЪЛИМИ ЎҚИТУВЧИЛАРИНИ ЧОЛҒУ ИЖРОЧИЛИГИ ОРҚАЛИ ЭСТЕТИК ТАФАККУРИНИ РИВОЖЛАНТИРИШНИНГ ТАШКИЛИЙ-ПЕДАГОГИК МАЗМУНИ - Саматова, Д.С. (SCIENCE and SOCIETY, 2023)
The article reveals the organizational and pedagogical content of the development of aesthetic thinking of future teachers of music education through instrumental performance. The significance and pedagogical aspects of instrumental performance are shown in the development of aesthetic thinking of future teachers of music education.